CD103+ T Cells Eliminate Damaged Alveolar Epithelial Type II Cells Under Oxidative Stress to Prevent Lung Tumorigenesis - Yu Xu; Haorui Luo; Jiahao Wang; Haifeng Liu; Luonan Chen; Hongbin Ji; Zimu Deng; Xiaolong Liu (Advanced Science)
Abstract The nexus between aging‐associated immune deteriorations and tumorigenesis of lung cancers remains elusive. In a mouse model with Med23 depletion in T cells (Med23 −/−), it is found a strong association between the decline of CD103+ T cells and spontaneous alveolar epithelial type II cell (AT2 cell)‐originated lung adenocarcinomas. The reduction of CD103+ T cells in the lung results in an accumulation of AT2 cells bearing oxidative damages, which appears to be the major origin of the lung adenocarcinoma. Functional experiments reveal CD103+ T cells can eradicate oxidative‐damage‐bearing AT2 cells as well as ROS‐dependent, KRAS (G12D)‐driven tumorigenesis. In vitro co‐cultures prove CD103+ T cells, especially CD103+ CD8+ T cells, exhibit a killing capacity that matches the oxidative stress level in the target cells. In aged animals, it is found the abundance of CD103+ CD8+ T cells in the lung declines with age, accompanied by an accumulation of oxidative‐damage‐bearing AT2 cells. Collectively, the study establishes the vital function of CD103+ T cells in surveilling epithelial cells under oxidative stress to prevent malignancies, and unravels a potential immuno‐dysregulation in the aged lung which contributes to tumorigenesis.